Risk Factors of Pulmonary Smear Positive Tuberculosis Incidence in Dili District Timor Leste 2014 - Jacinta dos Santos Guterres; Luh Putu Lila Wulandari; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2014)
Background and objectives: According to the WHO, the pulmonary tuberculosis (TB) in Timor-Leste is estimated to have the highest mortality rate in the region which is 45 per 100,000 populations. The aim of this study was to determine the risk factors for pulmonary tuberculosis in the Dili District. Methods: The study design was a case-control. Cases were patients with positive BTA pulmonary tuberculosis, and controls were non TB patients registered at two TB clinics (Motael and Bairro-Pite) and the three public health centers (Comoro, Formosa and Becora) in Dili, July 2013 - February 2014. Numbers of samples were 138 people consisting of 46 cases and 92 controls (1:2). Risk factors studied were smoking habits, contact with patients, nutritional status, family income, population density, sun lighting, ventilation and the use of firewood for cooking. Data were collected through interviews, observation and measurement. Bivariate analysis was performed to determine the similarity between cases and controls and to calculate the crude OR. Multivariate analysis with logistic regression was performed to determine adjusted risk factors that contribute to the increasing TB patients. Results: There were no significant differences between cases and control groups in age, gender, education and occupation (p>0.05). Bivariate analysis showed that the risk factors of pulmonary tuberculosis were the contact with patients (OR=2.809; 95%CI: 1.337-5.900), nutritional status (OR=2.380; 95%CI: 1.096-5.169), the sun lighting (OR=8.090; 95%CI: 3.468-18.872) and ventilation (OR=6.141; 95%CI: 2.709-13.924). Multivariate analysis showed that the significant risk factors were the contact with patients (OR=3.428; 95%CI: 1.455-8.075) and exposure to sunlight (OR=4.601; 95% CI: 1.336-15.845). Conclusion: The contact with patients and the exposure to sunlight were the risk factors for pulmonary TB of positive BTA at the Dili District of Timor Leste.